2016
DOI: 10.1002/eat.22624
|View full text |Cite
|
Sign up to set email alerts
|

Binge‐eating disorder in the Swedish national registers: Somatic comorbidity

Abstract: ObjectiveTo evaluate associations between binge‐eating disorder (BED) and somatic illnesses and determine whether medical comorbidities are more common in individuals who present with BED and comorbid obesity.MethodCases (n = 850) were individuals with a BED diagnosis in the Swedish eating disorders quality registers. Ten community controls were matched to each case on sex, and year, month, and county of birth. Associations of BED status with neurologic, immune, respiratory, gastrointestinal, skin, musculoskel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 34 publications
2
51
0
1
Order By: Relevance
“…Eating disorders are associated with somatic complications in multiple organ systems including the cardiovascular, gastrointestinal, musculoskeletal, dermatologic, endocrine, haematological, and neurological systems (Mehler & Brown, ; Mehler & Rylander, ; Thornton et al, ) as well as psychiatric comorbidities (Table S3). The more chronic and severe the eating disorder, the greater the likelihood of serious somatic complications (Westmoreland, Krantz, & Mehler, ).…”
Section: Truth 1: Many People With Eating Disorders Look Healthy Yetmentioning
confidence: 99%
“…Eating disorders are associated with somatic complications in multiple organ systems including the cardiovascular, gastrointestinal, musculoskeletal, dermatologic, endocrine, haematological, and neurological systems (Mehler & Brown, ; Mehler & Rylander, ; Thornton et al, ) as well as psychiatric comorbidities (Table S3). The more chronic and severe the eating disorder, the greater the likelihood of serious somatic complications (Westmoreland, Krantz, & Mehler, ).…”
Section: Truth 1: Many People With Eating Disorders Look Healthy Yetmentioning
confidence: 99%
“…Across clinical and larger community or epidemiological studies, EDs have shown significant, albeit highly variable, associations with various medical problems (Javaras et al, 2008;Kessler et al, 2013). One recent study, based on the Swedish population registry, reported that DSM-5 BED was associated with respiratory diseases, endocrine system diseases, musculoskeletal system and connective tissues diseases, and skin diseases (Thornton et al, 2017). One recent study, based on the Swedish population registry, reported that DSM-5 BED was associated with respiratory diseases, endocrine system diseases, musculoskeletal system and connective tissues diseases, and skin diseases (Thornton et al, 2017).…”
mentioning
confidence: 99%
“…A study of individuals with BED and obesity reports poorer scores in WRQOL domains, except physical function, as well as total WRQOL compared to individuals with only obesity (Rieger et al, 2005). Therefore, evidence suggests that having comorbid BED and obesity is associated with greater QOL impairment than having obesity alone, which may be due, in part, to the fact that individuals with BED typically present with high rates of psychiatric disorders (e.g., mood and anxiety disorders), somatic symptoms, and body image concerns (Grilo, White, & Masheb, 2009; Hrabosky, Masheb, White, & Grilo, 2007; Hudson et al, 2017; Thornton et al, 2017). …”
mentioning
confidence: 99%